Clinical usefulness of splanchnic oxygenation in predicting necrotizing enterocolitis in extremely preterm infants: a cohort study - E. Palleri; M. van der Heide; J. B.F. Hulscher; M. Bartocci; T. Wester; E. M.W. Kooi (BMC, 2023)
Abstract Background Impaired intestinal microcirculation seems to play an important role in the pathogenesis of necrotizing enterocolitis (NEC). A previous study showed that a SrSO2 < 30% is associated with an increased risk of developing of NEC. We aimed to determine the clinical usefulness of the cut off < 30% for SrSO2 in predicting NEC in extremely preterm neonates. Methods This is a combined cohort observational study. We added a second cohort from another university hospital to the previous cohort of extremely preterm infants. SrSO2 was measured for 1-2 h at days 2-6 after birth. To determine clinical usefulness we assessed sensitivity, specificity, positive and negative predictive values for mean SrSO2 < 30. Odds ratio to develop NEC was assessed with generalized linear model analysis, adjusting for center. Results We included 86 extremely preterm infants, median gestational age 26.3 weeks (range 23.0-27.9). Seventeen infants developed NEC. A mean SrSO2 < 30% was found in 70.5% of infants who developed NEC compared to 33.3% of those who did not (p = 0.01). Positive and negative predictive values were 0.33 CI (0.24-0.44) and 0.90 CI (0.83-0.96), respectively. The odds of developing NEC were 4.5 (95% CI 1.4-14.3) times higher in infants with SrSO2 < 30% compared to those with SrSO2 ≥ 30%. Conclusions A mean SrSO2 cut off ≥ 30% in extremely preterm infants between days 2-6 after birth may be useful in identifying infants who will not develop NEC.